Financing and advising early stage startups: The effect of angel investor subsidies - Marius Berger; Sandra Gottschalk (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
In recent years governments around the world have introduced policies to stimulate investments in early stage entrepreneurial companies, in particular investments by Angel investors. In this paper we study whether introducing subsidies to Angel investors has effects on startups' access to financial and managerial resources provided by Angel investors. Using data for a representative sample of entrepreneurial companies in Germany, we analyze the effect of the introduction of a major subsidy program for Angel investors in Germany. Having data before and after the introduction of the program allows us to use a difference-in-differences framework to examine the effect of the program on eligible companies. Our findings indicate that subsidies for Angel investors both increase the chances to receive financing from Angel investors (+36-67%), as well as the amount of financing received (+70-82%). In terms of managerial resources, we find no effects that are significantly different from zero. This result is in contrast to theoretical predictions suggesting negative effects of investment subsidies on the level of managerial support that companies receive. Exploring the mechanisms behind our results, we find that the policy stimulated entry by inexperienced investors, but also increased syndicate sizes of Angel investors in entrepreneurial companies.
Keywords: G28; G24; M13; O38; 330; Entrepreneurship Policy; Angel Investors; Venture Capital; Syndication